On the Ecclesiastical Mystagogy - St. Maximus the Confessor; Jonathan J. Armstrong (New York, USA St. Vladimir's Seminary Press, 2019)
"St Maximus the Confessor (c. 580-662) expounds the meaning of the Divine Liturgy in On the Ecclesiastical Mystagogy. He draws on the tradition of the Celestial Hierarchy by Dionysius the Areopagite, and influences the subsequent tradition, beginning with St Germanus of Constantinople's commentary. Maximus situates his understanding of the liturgy within his bold synthetic theological vision, seeing Christ the Logos of the God reflected and manifested in the logoi of created things. For Maximus, all things are interrelated-the material and the spiritual, God and man, earth and heaven-and cohere in Christ (cf. Col 1.17)"--
Keywords: Patristics (3Yde GdBHGFjGJs; History; Patrology